General and Food-Specific Inhibitory Control As Moderators of the Effects of the Impulsive Systems on Food Choices - Zhang, Xuemeng; Chen, Shuaiyu; Chen, Hong; Gu, Yan; Xu, Wenjian (Frontiers in Psychology, 2017)
The present study aimed to extend the application of the reflective-impulsive model to restrained eating and explore the effect of automatic attention (impulsive system) on food choices. Furthermore, we examined the moderating effects of general inhibitory control (G-IC) and food-specific inhibitory control (F-IC) on successful and unsuccessful restrained eaters. Automatic attention was measured using “the EyeLink 1000”, which tracked eye movements during the process of making food choices, and G-IC and F-IC were measured using the Stop-Signal Task. The results showed that food choices were related to automatic attention and that G-IC and F-IC moderated the predictive relationship between automatic attention and food choices. Furthermore, among successful restrained eaters, automatic attention to high caloric foods did not predict food choices, regardless of whether G-IC or F-IC was high or low. Whereas food choice was positively correlated with automatic attention among unsuccessful restrained eaters with poor F-IC, this pattern was not observed in those with poor G-IC. In conclusion, the successful restrained eaters had more effective self-management skills and their food choices were affected less by automatic attention and inhibitory control. Unsuccessful restrained eating was associated with poor F-IC (not G-IC) and greater automatic attention to HC foods. Thus, clinical interventions should focus on enhancing F-IC, not G-IC, and on reducing automatic attention to HC foods.